Effects of Preserving the Pulmonary Vagus Nerve Branches on Cough After Pneumonectomy During Video-Assisted Thoracic Surgery - Gu, Shaorui; Wang, Wenli; Wang, Xishi; Wu, Kaiqin; Zhang, Xin; Xie, Shiliang; Zhou, Yongxin (Frontiers in Oncology, 2022)
Background: Cough is one of the most common complications of early non-small cell lung cancer (NSCLC) after video-assisted thoracoscopic surgery (VATS). The vagus nerve plays an important role in pulmonary inflammation and the cough reflex, and has a certain impact on postoperative pulmonary complications. In this study, we attempted to reduce the incidence of postoperative chronic cough and other complications by preserving the vagus pulmonary branch. Patients and Methods: This study was a randomized controlled double-blinded trial of subjects and observers. A total of 158 NSCLC patients were enrolled. We randomly assigned 79 patients to Group A (pulmonary branch of vagus nerve preservation group) and 79 cases to Group B (conventional surgical treatment group). In the final analysis, 72 patients from Group A and 69 patients from Group B were included. The main outcome measure of the study was the occurrence of CAP or other postoperative complications within five weeks. This trial was registered with ClinicalTrials.gov (number NCT03921828). Results: There was no significant difference in preoperative general clinical data between the two groups. There was no significant difference in other pulmonary and cardiovascular complications between the two groups, including pulmonary infection (2.78% vs. 8.70%, P = 0.129), atelectasis (1.39% vs. 0%, P = 0.326), pleural effusion (2.78% vs. 1.45%, P = 0.585), persistent pulmonary leakage (2.78% vs. 2.90%, P = 0.965), arrhythmia (2.78% vs. 1.45%, P = 0.585), and heart failure (0% vs. 1.45%, P = 0.305). The incidence of CAP in Group A was significantly lower than that in Group B (13.89% vs. 30.43%, P = 0.018). The LCQ-MC scores in Group A were significantly higher than those in Group B at two and five weeks after operation (P<0.05). Univariate and multivariate analysis showed that the risk factors for postoperative CAP were surgical side (right lung), surgical lung lobe (upper lobe), preservation of pulmonary branch of the vagus nerve during operation, and duration of anesthesia. Conclusions: Preserving the pulmonary branch of the vagus nerve during VATS in patients with stage IA1-2 NSCLC can reduce the incidence of postoperative CAP.